Family environment, coping, and mental health in adolescents attending therapeutic day schools. Issue 7 (23rd August 2014) - Rodriguez, Erin M.; Donenberg, Geri R.; Emerson, Erin; Wilson, Helen W.; Brown, Larry K.; Houck, Christopher
ABSTRACT: Objective: This study examined associations among family environment, coping, and emotional and conduct problems in adolescents attending therapeutic day schools due to mental health problems. Methods: Adolescents ( N  = 417; 30.2% female) ages 13–20 ( M  = 15.25) reported on their family environment (affective involvement and functioning), coping (emotion‐focused support‐seeking, cognitive restructuring, avoidant actions), and emotional and conduct problems. Results: Poorer family environment was associated with less emotion‐focused support‐seeking and cognitive restructuring, and more emotional and conduct problems. Emotional problems were negatively associated with cognitive restructuring, and conduct problems were negatively associated with all coping strategies. Cognitive restructuring accounted for the relationship between family environment and emotional problems. Cognitive restructuring and emotion‐focused support‐seeking each partially accounted for the relationship between family functioning and conduct problems, but not the relationship between family affective involvement and conduct problems. Conclusions: Findings implicate the role of coping in the relationship between family environment and adolescent mental health.